-6x-5(6x+2)=-10

Simple and best practice solution for -6x-5(6x+2)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-5(6x+2)=-10 equation:



-6x-5(6x+2)=-10
We move all terms to the left:
-6x-5(6x+2)-(-10)=0
We add all the numbers together, and all the variables
-6x-5(6x+2)+10=0
We multiply parentheses
-6x-30x-10+10=0
We add all the numbers together, and all the variables
-36x=0
x=0/-36
x=0

See similar equations:

| -0,8a-8=0.2a | | b4− 2= 1 | | 5x+12=7x-9 | | .5(.5x-8)-5=4 | | 16+2t=3/2t+9 | | 0.753=4^x | | 4y=7/1 | | 5x+12-2x+6=-15 | | x/2.50=0.10 | | 3-4(x+1)=159 | | 5r=3/4 | | 2(3+y)=18 | | h=1/2(980*20^2) | | B=35.00-0.20x | | 4.9t^2-5t-760=0 | | 6(2x-5=-(2+4) | | 3(x-8)=7x+9 | | -9x+27=18 | | 2(2y/3-2/3)=0 | | 25x3-3x=0 | | 7=11x+19 | | 7p=10=38 | | 6p+8=12+5p | | x-9/4+x+7/3=7/4 | | 7(v-2)-3=-5(-3v+4)-2v | | (-3x-9)(4x+28)=0 | | 3x=24;x | | 4(z+7)-5=8z-5 | | u/7-1.6=-12.8 | | 2/5x+8=-4 | | 3/4x+5/8=3/2 | | 7(71/3-21/3y)+2y=-13 |

Equations solver categories